Brahna Trager papers - Trager, Brahna
Correspondence, writings, speeches, reports, conference material, printed matter, and other papers relating to her work in home health care. Includes material concerning her work with the Senate Special Committee on Aging; California Bureau of Crippled Children Services; Long-Term Care Research Project of the University of California at Berkeley; and San Francisco Home Health Service. Documents her search for international approaches to home health care and her editorial work for Home Health Care Services Quarterly. Also includes correspondence, biographical material, photographs, and papers relating to her fiction writing.
Home health care administrator, health care policy analyst, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: California. -- Bureau of Crippled Children Services; United States. -- Congress. -- Senate. -- Special Committee on Aging; San Francisco Home Health Service; University of California, Berkeley -- Long-Term Care Research Project; Home health care services quarterly; Home care services; Home care services -- United States; Medical care; Medical care -- United States; Authors; Health care administrators; Health care policy analysts